Impact of Gender Inequity on Women Surgeons in the Professional Setting - Onyiego, Alexandra; Davids, Jennifer S. (Clinics in Colon and Rectal Surgery, 2023)
The concept of equity ensures that each individual is given the environment, treatment, and resources needed to reach an equal outcome to those around them. Equity is central to initiatives for advancing diversity and inclusion among physicians. This article will identify key barriers to equity that women surgeons face within the professional setting. More specifically, inadequate female representation, discrimination in the form of unconscious gender bias and microaggressions, and sexual harassment will be explored regarding their continued threats to gender equity, as well as constructive ways to mitigate these effects.
Keywords: women in surgery; implicit gender bias; equity in surgery